Serum Sema4D levels are associated with lumbar spine bone mineral density and bone turnover markers in patients with postmenopausal osteoporosis - Zhang, Yiyuan (Int J Clin Exp Med, 2015)
To investigate the association of serum semaphorin 4D (Sema4D) levels with lumbar spine bone mineral density (BMD) and bone turnover markers in patients with postmenopausal osteoporosis (PO). Lumbar spine BMD was measured by dual-energy X-ray absorptiometry in 257 PO patients (aged from 50 to 75) and 90 healthy controls (aged from 51 to 83). Serum Sema4D, BAP, BGP and TRACP-5b levels were measured by enzyme linked immunosorbent assay. Serum cross linked N-telopeptides of type I (NTX), 25-hydroxyvitamin D (25(OH)D) and N-mid fragment of osteocalcin (N-MID-OT) levels were measured using automated electrochemiluminescence system. Sema4D level was significantly higher in PO women compared to healthy controls (1.40±0.33 vs. 0.58±0.18 μg/L, P=0.006). Sema4D level was positively correlated with serumTRACP-5b and NTX levels and negatively correlated with lumbar spine BMD and serum BAP and BGP levels. There were no correlations between Sema4D level and age, body mass index, and serum 25(OH)D and N-MID-OT levels. Lumbar spine BMD (β=-0.354, P<0.001) and serum BAP level (β=0.127, P=0.019) were independent predictors of serum Sema4D level in PO patients. Sema4D may be involved in the pathogenesis of PO and play a critical role in bone formation and resorption. Sema4D may represent a novel therapeutic target for treatment of PO and function as a predictive indicator of PO.